MONETARY CREDIBILITY AS A SOCIAL VALUE IN THE CONTEMPORARY MONETARY LAW AND CENTRAL BANIKNG LAW - Dimitrijević, Marko B. (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2023)
Emphasizing the importance of credibility in public monetary management has been present as a basic axiological subordinate to the norms of monetary law since its formation as an independent and independent branch of the legal order. It is interesting to point out that although the content and direction of the monetary activities of the central bank, as the basic subject of monetary law, were mixed over time and adapted to new circumstances, which resulted in the expansion of the regulatory competences of the central bank, the emergence of new theories about the legal custody of money and the determination of the limits of legal responsibility in the work of monetary agents, credibility in its meaning remains the same as the final monetary legal thought of each eoph and as the ideal and ultimate purpose of this branch of law with all its institutes, principles and categories. Contemporary monetary law, which has sui generis legal sources, even in today’s unstable social conditions, proves to be extremely flexible and grateful for transformation into the law of necessity, when extraordinary circumstances require it in a value context, it does not make relativization and credibility as the primordial value of public management of every institution, so the central bank remains in the central position.